A new bioreactor design for culturing basidiomycetes: Mycelial biomass production in submerged cultures of Ceriporiopsis subvermispora. (12th October 2017) - Domingos, Marcelo; Souza-Cruz, Priscila Brasil de; Ferraz, André; Prata, Arnaldo Márcio Ramalho
Highlights: A single device was developed for agitation and air injection into a bioreactor for aerobic fermentations. Rounded surfaces of agitation device avoid adherence during submerged filamentous fungi cultivation and increases homogeneity. High homogeneity of culture broth promotes decrease in chlamydospores formation during submerged cultivation of a basiomycete. A specially designed bioreactor provides higher fungal biomass concentration compared to STR bioreactor. Abstract: Oxygen transfer in submerged cultures of basidiomycetes is a key factor for efficient fungal growth. However, conventional stirred tank and airlift reactors are not utterly suitable for basidiomycetes culturing because they promote high shear stress to the mycelial hyphae and favor rapid agglomeration of mycelial pellets, compromising the diffusion of oxygen to the inner side of mycelium. We describe an original reactor design that overcome some of the limitations of conventional bioreactors used in submerged cultures of basidiomycetes. The strategy was to use a mechanism that permits simultaneous axis rotation and air injection, being the agitation promoted by an L-shaped tube. Adherence of mycelium and shear stress is avoided once only rounded surfaces exist inside the bioreactor. Ceriporiopsis subvermispora was selected as a model basidiomycete. The most productive system employed sucrose/corn steep liquor as the culture medium and pulsed addition of sucrose during the culturing. This approach provided efficient mycelial growth (maximum of 14.1 g·L –1 ), and avoided pH increase and pellet agglomeration throughout the fungal cultivation for 7 days, resulting in a biomass productivity of 1.72 g·L –1 ·day –1 . Microscopic evaluation of chlamydospores accumulation in the grown mycelium confirmed that minimal fungal stress occurred in the cultures performed in the new designed bioreactor, contrasting with cultures carried out in conventional stirred tank bioreactors.